Manufacturing process planning : a practical approach for mechanical engineering - Abellán-Nebot, José V.; Vila Pastor, Carlos; Siller Carrillo, Héctor Rafael (John Wiley & Sons, Inc., 2025)
"Process planning refers to all activities that are out in a manufacturing company to produce a product given the technical drawing from the design office. Any product starts from a technical drawing and requires a process planning methodology to define all the steps required at shop-floor level to correctly produce the product. It's a topic that is typically taught at the advanced undergraduate or graduate level in Mechanical or Industrial Engineering programs, after students have completed an introductory/fundamental manufacturing course."--